Anxiety dan Kesehatan Mental dalam Al-Qur’an: Eksplorasi Konsep Khauf, Huzn, dan Sakinah sebagai Landasan Kesehatan Mental Spiritual - Anggun Vilanda Septiandariani; Syafieh Syafieh; Cut Fauziah (Al-Widad, 2025)
Mental health has become a global issue that is gaining increasing attention due to the increasing prevalence of anxiety disorders and psychological stress. From an Islamic perspective, the Qur'an not only serves as spiritual guidance but also offers concepts relevant to human mental health. This study aims to explore the concepts of khauf (fear), huzn (sadness), and sakinah (peace of mind) in the Qur'an as the conceptual foundation for spiritual mental health. The study used a qualitative method with a thematic interpretation (maudhu'i) approach to Qur'anic verses related to these three concepts. Data were analyzed using both classical and contemporary approaches and linked to modern mental health theories. The results show that the Qur'an acknowledges negative emotions, such as fear and sadness, as a natural part of human life. However, the Qur'an offers a mechanism for psychospiritual transformation through faith, dhikr (remembrance of God), tawakkul (relief), and a strong relationship with God, thus giving rise to a state of sakinah. The concepts of khauf and huzn in the Qur'an are not positioned as mere psychological disorders, but rather as existential experiences that can be managed through a spiritual approach. These findings indicate that the Qur'anic concepts of khauf, huzn, and sakinah have significant relevance in developing an Islamic-based spiritual mental health paradigm.